The Special Purpose Entity of the Poznań University of Economics and Business (the Spv of the Pueb) as an Example of Support for Research Commercialization in Poland - Szulczewska-Remi, Aleksandra (Studia Oeconomica Posnaniensia, 2016)
The last twenty years in Poland's history have seen substantial economic growth, however in terms of innovation Poland remains at the tail end of developed countries. It is therefore vital to develop effective mechanisms for furthering innovation, academic entrepreneurship and to support collaboration between business and science. Therefore the paper focusses on the theoretical framework of knowledge commercialization models amongst international universities. The next section examines Polish contributions to the current academic discussion based on literature review and case study example from Poznań University of Economics and Business. In this context Poland's amended Higher Education Act has given universities a great deal of leeway in creating a proper model for transferring knowledge and technology. In response to new legislation, the PUEB has taken advantage of a Spin-Tech programme donation becoming Poland's only university of economics to have set up a special purpose entity. The SPV of the PUEB is well-poised to coordinate interdisciplinary student and faculty projects intended for business use, assess commercialization potential by conducting innovation audits, offer consultations on external fund raising, manage intellectual property and professionally assess project value. Thus it has fulfilled the growing need for effective models for commercializing scientific research examples in Central Eastern Europe reported by other authors.